SPE European Formation Damage Conference 2011
DOI: 10.2118/143643-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Residual Oil Saturation on the Propagation of Regular, Gelled, and In-Situ Gelled Acids inside Carbonate Formations

Abstract: In oil fields, serious difficulties with acid-induced sludge, a major source of well damage, can vary from a viscous, stable emulsion. A chemical analysis of sludge shows that hydrochloric acid (HCl) is present in the sludge structure. Also, Fe(III) ions in HCl formulations can cause a large amount of sludge. Even though ferric ion could not be detected in the oil phase or in the sludge, it induces sludge mainly because it works as a phase-transport catalyst for HCl. Therefore, the objective of this study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Literature survey shows contrasting results as to how residual oil affects pore volume to breakthrough. Gomaa et al (2011) showed that as flow rate increased, higher pore volumes of regular acid were required to break through cores with residual oil saturation. Shukla et al (2006) claims that residual oil saturations in carbonate cores had little effect on the acidizing process and that these cores have the same wormholing effect as cores completely saturated with water.…”
Section: Effect Of Oil Saturation While Acidizing Carbonate Rocksmentioning
confidence: 99%
“…Literature survey shows contrasting results as to how residual oil affects pore volume to breakthrough. Gomaa et al (2011) showed that as flow rate increased, higher pore volumes of regular acid were required to break through cores with residual oil saturation. Shukla et al (2006) claims that residual oil saturations in carbonate cores had little effect on the acidizing process and that these cores have the same wormholing effect as cores completely saturated with water.…”
Section: Effect Of Oil Saturation While Acidizing Carbonate Rocksmentioning
confidence: 99%